Development of a training stand based on the MKN1063 cabinet for the practical preparation of students in electrical installation and automation - Dudnik, A.; Hryshchenko, V.; Liktey, V.; Polovko, S.; Karlova, O. (Energy and Automation, 2025)
The article presents the results of a study aimed at addressing the problem of insufficient practical training of students in electrical engineering specialties in the areas of installation, commissioning, and operation of electrical equipment. An analysis of the industrial internship conducted at the company LLC "SichEnergo" revealed that a significant portion of students lack the necessary competencies to work with cabinet electrical equipment. In particular, difficulties were identified during installation work in the confined spaces of electrical cabinets, insufficient skills in cable routing, installation of modular equipment on DIN rails, execution of switching operations, and connection of circuit breakers, relays, contactors, PLCs, and other apparatus. A separate methodological issue was the impossibility of organizing group training directly at real, operating cabinets due to limited access to the working area. A review of current research in the field of engineering education showed that, despite the development of VR/AR technologies, digital simulators cannot fully replace physical installation stands. Virtual tools are effective for visualizing and familiarizing students with system construction principles; however, detecting and correcting cable connection defects, proper use of tools, organizing the installation space, and performing operations in real conditions require hands-on work with actual components. Therefore, the optimal training model is a combination of digital technologies and physical constructions that can accurately simulate the production environment. To address this issue, a universal training installation stand was developed based on the industrial MKN1063 electrical cabinet. The stand’s design includes typical electrical installation components, programmable logic controllers, modular relays, circuit breakers, communication modules, and other equipment, allowing students to practice both basic and advanced training scenarios aligned with modern production requirements, including Smart Grid and IoT infrastructure. The stand is equipped with transparent side panels, enabling the entire group to simultaneously observe the installation process, analyze execution techniques, and correct errors. A key innovation of the stand is the ability to perform installation first on a horizontally placed panel and then on its vertical placement inside the cabinet. This approach allows for accurate replication of real production conditions, practice of the full installation cycle, and development of competencies required for working with cabinet equipment. The modular layout provides flexibility in configuring training tasks, including disassembly, troubleshooting, and maintenance operations. Results of the trial implementation demonstrated increased accuracy in performing installation tasks, improved teamwork skills, and higher compliance with electrical safety requirements. Key words: installation of electrical equipment, control cabinet, panel, stand